Operations strategy of a grocery chain in Malaysia - Abdullah, Nur Anisah (2013)
Convenient stores or mini-marts are becoming a common sight in many residential areas as well as town centers. They are usually located at the corner of a block of business establishments. This category of convenient stores is typically characterized by its size, the range of products they carry, the target market and location, and its pricing strategy. This type of business model is flourishing as the number of players and the number of stores each player establishes has increased tremendously over the last 10-12 years. Before this wave of enterprising ventures, the only commonly known household name for smallish-neighbourhood convenient store was 7-eleven. We now saw more popular grocery chains such as 99 Speedmart®, Econsave, SaveMore, Billion and others. What is their success story? This case study explores the operations strategy of one the most aggressively growing grocery chain in Malaysia.